Wind loads on flat roofs of low-rise buildings with rounded leading edge. (3rd April 2019) - Dong, Xin; Ding, Jiemin; Jiao, Changke
ABSTRACT: Using wind tunnel experiments, wind loads on the flat roofs of low-rise buildings with rounded leading edges were investigated under the effects of separation bubbles and conical vortices. First, pressure distributions on the flat roofs were presented. Second, total uplift forces and overturning moments were calculated by the introduction of area-averaged pressures. Third, eigenvalues and eigenvectors of fluctuating pressure were obtained by proper orthogonal decomposition. Finally, wind pressure characteristics at the rounded edges were examined. The results indicate that after the use of a rounded leading edge, suctions induced by separation bubble and conical vortices increase near the chamfer, decrease beneath the vortices, and stay invariant far from the leading edge. The area involved and the energy of pressure fluctuation decrease, with the largest decrease occurring on a flat roof with a larger fillet radius under conical vortices. In addition, the maximum decreases in peak total uplift forces and overturning moments reach 11% and 62%, respectively, and appear at skewed flows. The maximum suction and low-frequency spectral peak of pressure fluctuations at the rounded leading edge may exceed those at the neighboring region. As the fillet radius increases, the maximum suction and low-frequency pressure fluctuation energy at the chamfer decrease.